The Transformative Power of Translation: Mediating Cultural Nuances and Mitigating Narrative Asymmetry in Shaping China’s Global Image through Foreign Media - Shang, Junzhi (International Journal of Social Sciences and Public Administration, 2025)
This study explores the multifaceted and transformative role of translation in navigating cross-cultural communication complexities, with a specific focus on its capacity to mediate cultural nuances and mitigate narrative asymmetry in foreign media representations of China. As a critical interface between China’s socio-political discourse, cultural heritage, and global audiences, translation transcends mere linguistic conversion to become a strategic mechanism that shapes, reframes, and contextualizes narratives. The research identifies how translational practices-whether adaptive, contextual, or collaborative-can address inherent challenges such as culturally specific terminology, ideological bias, and unequal global media power dynamics. By analyzing case studies spanning political discourse, cultural content, and public diplomacy, it argues that sophisticated translational strategies are pivotal in fostering a more balanced, nuanced, and authentic portrayal of China in international media landscapes. Ultimately, the study concludes that harnessing translation as a transformative tool is essential for bridging cognitive gaps, reducing narrative disparities, and constructing a globally resonant image of China that reflects its complexity and dynamism.